Garantismo y publicismo en el proceso civil: un enfoque analítico - Cavani, Renzo; Castillo, Álvaro (Pontificia Universidad Católica del Perú, 2021)
This essay uses an analytic methodology in order to differentiate three approaches in the classical debate between activist (publicist) and adversarial (guarantee) models in the continental tradition of civil procedural law: the historical, philosophical and institutional approach. It is showed that each one of them has different premises of discussion and also allows to reach particular consequences. We defend a proposal to distinguish between the activist model and the adversarial model from a philosophical point of view by identifying the political theory premises that are in their foundations. In the activist model, the State’s function is to be a provider for the protection of fundamental rights and, therefore, the judicial process is conceived as an instrument of the jurisdiction in order to achieve its public goals. On the other hand, in the adversarial model, the State’s function assumes an abstentionist- type in order to preserve fundamental rights and hence, far from being and nstrument of judicial power, the judicial process is conceived as a citizen’s guarantee oriented to control that very power.

El presente texto echa mano de una metodología analítica para diferenciar tres discursos en el clásico debate entre publicismo y garantismo en el contexto del derecho procesal civil en la tradición continental: el histórico, el filosófico y el institucional. Se muestra que cada uno de ellos tiene diferentes premisas de discusión y, también, que permiten a llegar a consecuencias particulares. Así, defendemos una propuesta para distinguir el modelo publicista del garantista en el discurso filosófico identificando las premisas teórico-políticas que les sirven de base. En el caso del modelo publicista, la función del Estado es la de ser un prestador para la tutela de los derechos fundamentales o garantías y de ahí se desprende que el proceso sea visto como herramienta de la jurisdicción para concretar sus fines. Por su parte, en el caso del modelo garantista, la función del Estado asume un papel de abstención a fin de respetar los derechos fundamentales o garantías y, por ello, el proceso, lejos de ser un instrumento del poder jurisdiccional, es asumido como una garantía del ciudadano orientada a controlar dicho poder.
Garantism and Publicism in Civil Procedural Law: An Analytical Approach
Keywords: Activist model; Adversarial model; Publicist model; Guarantee model; Constitutional model of procedure; Constitutionalism; Constitutional guarantee; Publicismo; Garantismo; Modelo constitucional de proceso; Constitucionalismo; Garantía constitucional; https://purl.org/pe-repo/ocde/ford#5.05.01